Evaluation of the Quality of Ready-Mixed Concrete Used in Building Controlled Structures after Electronic Concrete Monitoring System - Çelik, Mehmet Taha; Yıldız, Servet; Emiroğlu, Mehmet (Hibetullah KILIÇ, 2024)
It is of great importance that the buildings are built as earthquake resistant in our country where there is an earthquake risk. Iron and concrete designs are at the forefront of the determining parameters in the earthquake resistance of buildings. With the widespread use of ready mixed concrete system in our country, great improvements have been achieved in concrete quality. The quality of concrete is directly related to its production properties as well as its compressive strength. Accordingly, the production of high-quality and high-quality ready-mixed concrete in the construction sector has come to the fore in recent years. According to the building inspection law that came into force, the sensitivity of building inspection organizations on the strength of concrete classes has also increased. The Electronic Concrete Monitoring System (EBIS), in which concrete samples are monitored electronically for the first time in the world, was put into use in order to prevent abuses in the ready mixed concrete inspections of the buildings. Although the results obtained show that there is no problem in the compressive strength results of the ready mixed concrete used in the buildings under construction control, the points to be considered in concrete quality were encountered and these issues were emphasized.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri